Analisis Karbon Monoksida (CO) Menggunakan Metode Gaussian Plume di Persimpangan Margorejo Ahmad Yani Surabaya - Naufal, Muhammad Taffarel Faridzi; Munfarida, Ida; Yusrianti, Yusrianti (Dampak, 2023)
Carbon monoxide is a pollutant that can interfere with human life and the environment. One of the sources of carbon monoxide pollutants comes from motor vehicle emissions. Heavy traffic can result in poor air quality. The city of Surabaya is the largest metropolitan city after Jakarta. One of the heavy traffic in the city of Surabaya is the Margorejo Ahmad Yani intersection, this intersection is the link between Surabaya and Sidoarjo. The purpose of this study is to determine the results of carbon monoxide in the field, predict the Gaussian Plume model, and calculate the results of field data validation and model data. Determination of the location of the sampling point is based on SNI 19-7119.6.9, 2005 section 6, so that a total of 6 sampling points can represent the intersection. The average yield of carbon monoxide in the field on Saturday, Sunday, and Monday in a row is 14,336 μg/m3, 13,615 μg/m3, 16,881 μg/m3. The distribution distance of the Gaussian model simulation on Saturday Morning; Afternoon; The afternoon in a row is 54 m; 64; 76 m, Sunday Morning; Afternoon; The afternoon in a row is 34 m; 53 m; 54 m, Monday Morning; Afternoon; The afternoon in a row is 62 m; 65 meters; 62 m. The results of field data validation and model data with the MAPE formula are 15.17%. Keywords: motor vehicles, carbon monoxide, gaussian  ABSTRAK Karbon monoksida merupakan polutan yang dapat mengganggu kehidupan manusia dan lingkungan. Salah satu sumber pencemar karbon monoksida berasal dari emisi kendaraan bermotor. Lalu lintas yang padat dapat mengakibatkan kualitas udara yang buruk. Kota Surabaya merupakan kota metropolitan terbesar setelah Jakarta. Salah satu lalu lintas yang padat di Kota Surabaya adalah simpang Margorejo Ahmad Yani, simpang ini merupakan penghubung antara Surabaya dengan Sidoarjo. Tujuan dari penelitian ini adalah untuk mengetahui hasil karbon monoksida di lapangan, memprediksi model Gaussian Plume, dan menghitung hasil validasi data lapangan dan data model. Penentuan lokasi titik pengambilan sampel didasarkan pada SNI 19-7119.6.9 tahun 2005 pasal 6, sehingga sebanyak 6 titik pengambilan sampel mewakili titik potong tersebut. Hasil rata-rata karbon monoksida di lapangan pada hari Sabtu, Minggu, dan Senin berturut-turut adalah 14.336 μg/m3, 13.615 μg/m3, 16.881 μg/m3. Jarak distribusi simulasi model Gaussian pada Sabtu Pagi; Sore; Sore berturut-turut adalah 54 m; 64; 76 m, Minggu Pagi; Sore; Sore berturut-turut adalah 34 m; 53 m; 54 m, Senin Pagi; Sore; Sore berturut-turut adalah 62 m; 65 meter; 62 m. Hasil validasi data lapangan dan data model dengan rumus MAPE sebesar 15,17%. Kata kunci: kendaraan bermotor, karbon monoksida, gaussian